Contribution of preoperative gut microbiota in postoperative neurocognitive dysfunction in elderly patients undergoing orthopedic surgery - Bi, Jiangjiang; Xu, Yifan; Li, Shiyong; Zhan, Gaofeng; Hua, Dongyu; Tan, Juan; Chi, Xiaohui; Xiang, Hongbing; Guo, Fengjing; Luo, Ailin (Frontiers in Aging Neuroscience, 2023)
Objective: To investigate the role of gut microbiota and metabolites in POCD in elderly orthopedic patients, and screen the preoperative diagnostic indicators of gut microbiota in elderly POCD. Method: 40 elderly patients undergoing orthopedic surgery were enrolled and divided into Control group and POCD group following neuropsychological assessments. Gut microbiota was determined by 16S rRNA MiSeq sequencing, and metabolomics of GC-MS and LC-MS was used to screen the differential metabolites. We then analyzed the pathways enriched by metabolites. Result: There was no difference in alpha or beta diversity between Control group and POCD group. There were significant differences in 39 ASV and 20 genera bacterium in the relative abundance. Significant diagnostic efficiency analyzed by the ROC curves were found in 6 genera bacterium. Differential metabolites in the two groups including acetic acid, arachidic acid, pyrophosphate etc. were screened out and enriched to certain metabolic pathways which impacted the cognition function profoundly. Conclusion: Gut microbiota disorders exist preoperatively in the elderly POCD patients, by which there could be a chance to predict the susceptible population.